Technocalyps - Theys, Frank (Belgium : Votnik, 2006)
A documentary about transhumanism. The latest findings in genetics, robotics, artificial intelligence, bionics and nanotechnology appear in the media every day, but with no analysis of their common aim: that of exceeding human limitations and creating new, higher forms of life. While some scientists raise the alarm, others want to speed up the advances to be alive when immortality will be at hand, to become transhumans themselves. Is this an updated version of age-old dreams or are we for the first time confronted with the prospect to turn these dreams into reality?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films